Upaya Penanaman Nilai-Nilai Pendidikan Agama Islam Pada Anak Usia Dini Di Paud Pelita Hati - Hostini, Lesti (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to find out the efforts to instill the values of Islamic religious education in early childhood at Pelita Hati PAUD. The methodology in this study uses descriptive qualitative. The results of the study show that the inculcation of Islamic religious values in early childhood at Pelita Hati Early Childhood Education is an inculcation of Islamic religious values which is carried out through the process of managing PAUD activities. There are 3 levels of achievement in the development of instilling Islamic religious values, namely the level of achievement in the development of aqidah, by introducing religious chants, the second level of achieving moral development, which can be in the form of praying, loving fellow human beings, protecting the environment and so on, and the third the level of achievement of the development of worship is by teaching children to learn to pray.